Vibrations of an orthotropic plate with point supports subjected to a moving force - ZAKĘŚ, Filip (Engineering Transactions, 2023)
We investigate the dynamic behavior of a rectangular orthotropic plate loaded with the concentrated force moving with constant speed along the structure. In this work, we consider two types of plates in terms of boundary conditions. In the first case, we assume that the plate is simply supported on all of its edges with a number of point supports arbitrarily located in its area, and in the second one, we look at a two-span bridge plate with arbitrarily oriented intermediate linear support. Solutions for both cases are obtained by replacing the original structure with a single-span plate subjected to a given moving load and redundant forces situated in positions of removed intermediate supports. Redundant forces are obtained by the application of Volterra integral equations for the simply supported plate, and finite difference discretization and the Newmark method for the bridge plate. Two numerical examples are given to prove the effectiveness of the presented approach.